Varietal led ecological resilience through KRL 210 in salt stressed wheat - Sheoran, Parvender; Kamboj, Paras; Kumar, Arvind; Parjapat, Kailash; Barmana, Arijit; Kumar, Ashwani; Singh, Ranjay K; Mandal, Subhasis; Rohilla, P P; Singh, S K; Chahal, V P; Sharma, P C (Indian Farming, 2022)
The intervention through inclusion of tolerant varieties can be an important strategy to counter yield reduction under salty ecology. Significant change in farmers’ perception has been noted towards cultivating salt tolerant wheat variety KRL 210 in problematic areas dominated by sodic soils and high RSC waters. This enhanced ecological resilience has helped to stabilize wheat production and generate additional income to the farmers under the existing levels of sodicity stress. The fields’ insights will certainly help convincing the developmental agencies and receive government attention while formulating the policy guidelines for wheat developmental programme in salt-affected ecologies.